E Fragrante Cafe / Muhammad Faiz Noor Shahfizal, Siti Nursyafiqah Mohd Rode, Fifi Ezette Shahirul Shahzal, Muhamad Indera Shanizam Mohd Yunos, Muhammad Shafiq Aiman Zaharuddin and Muhamad Firdaus Mokhtar - Noor Shahfizal, Muhammad Faiz; Mohd Rode, Siti Nursyafiqah; Shahirul Shahzal, Fifi Ezette; Mohd Yunos, Muhamad Indera Shanizam; Zaharuddin, Muhammad Shafiq Aiman; Mokhtar, Muhamad Firdaus (2015)
Entrepreneurship is a process of innovation and new venture creation through four dimension which is include individual, organization, environment and institution. Entrepreneurs are individual who actively from are lead their own business nurture them for a growth and prosperity. In order to form a business, there are quite numbers of phase that should be understood and develop by entrepreneur.